Chipless-RFID: A Review and Recent Developments - Cristian Herrojo; Ferran Paredes; Javier Mata-Contreras; Ferran Martín (Sensors, 2019)
In this paper, a review of the state-of-the-art chipless radiofrequency identification (RFID) technology is carried out. This recent technology may provide low cost tags as long as these tags are not equipped with application specific integrated circuits (ASICs). Nevertheless, chipless-RFID presents a series of technological challenges that have been addressed by different research groups in the last decade. One of these challenges is to increase the data storage capacity of tags, in order to be competitive with optical barcodes, or even with chip-based RFID tags. Thus, the main aim of this paper is to properly clarify the advantages and disadvantages of chipless-RFID technology. Moreover, since the coding information is an important aspect in such technology, the different coding techniques, as well as the main figures of merit used to compare different chipless-RFID tags, will be analyzed.